Domestic product versus personal income convergence, within EU and euro area - Dan Constantin Olteanu (Romanian Academy, National Institute for Economic Research, 2020)
This study aims to assess the extent to which the economic integration process of the EU and the Eurozone, expressed by the convergence of GDP per capita, is reflected in the convergence of economic well-being of households, revealed by income and consumption, during the last 20 years (2000-2019). We find that, first of all, the convergence process of GDP per capita is strongly correlated with that of household income and consumption, both for the EU and the Eurozone level. This proves that GDP remains a relevant determinant of economic well-being of population. Secondly, our analyzes show that the socio-economic convergence process has been mainly supported by the growth of emerging Eastern European economies. Together with the declining Southern countries, they are converging to a level below the current EU average. On the other side are the developed countries of Central and Northern Europe, which include a core with constant developments well above the EU average and a group of poor performing countries, which tend to approaches the EU average. For the group of initial euro area members, the alternation of convergence/divergence tendencies, together with the coefficient of variation in 2019 located very close to the 2000 one, indicate a lack of convergence during this period, both for GDP and household income.
Keywords: O47; I31; O52; 330; growth convergence; well-being convergence; household income and consumption; EU integration